PENGARUH KEPERCAYAAN, PERSEPSI HARGA, KUALITAS PELAYANAN DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN LAZADA DI JAKARTA TIMUR - Suryani Chodidjah (Panorama Nusantara, 2021)
This study aims to determine the effect of trust, price perception, service quality, and brand image on consumer satisfaction, the research population is people who have made purchases through LAZADA buying and selling services. Proportional sampling technique is simple random sampling with 100 respondents. Primary data were collected through a questionnaire using a Likert scale model that had been tested for validity and reliability. The data analysis technique used is multiple linear regression. The results of this study simultaneously Trust, price perception, service quality, and brand image on consumer satisfaction is 65.4%, with variable trust and brand image influence on consumer satisfaction, and the variable perception of price and service quality does not affect consumer satisfaction LAZADA.